Mapping Ecosystem Conservation Priority Based on Social Assessment, a Tool to Assist Land Use Planning - Ahumada, María Luján; Cavallero, Laura; Easdale, Marcos Horacio; Tittonell, Pablo Adrian; Lopez, Dardo Ruben (Wiley, 2025)
The lack of planning regarding the spatial location and extent of different anthropogenic activities (such as agricultural production, biodiversity conservation, tourism, and urbanization) results in unsustainable land use and occupancy. Unplanned land use change threatens the supply of ecosystem services (ES) and thus, human well-being. Reversing this requires participatory land use planning that includes the stakeholders who inhabit the territory. Here, we analyze the social assessment of ES and its spatial representation on a map of Ecosystem Conservation Priority (ECP). In participatory workshops, we used the Analytic Hierarchy Process to characterize the assessment of stakeholders about the ES provided by forest landscapes. Among the ES analyzed, all stakeholders prioritized ES associated with hydrological regulation (Watershed Conservation Potential). Most stakeholders assigned a lower value to provisioning ES than to supporting and regulating ES, except for Agribusiness and Farmers. In addittion, we integrated social assessments with spatially explicit information through Multicriteria Modeling which allowed us to map ECP. Finally, we generated a map of consensus and dissent regarding ECP which can be used as input for land use planning. The highest consensus levels (86.45%) were mainly located in the upper watershed. In contrast, lower consensus levels (7.88%) were located mainly in plain areas of degraded and fragmented native forests. These results suggest that the ongoing transformation of forest ecosystems is linked to tensions that prioritize urbanization and agricultural activities as opposed to agroforestry land uses. Efforts to prevent the degradation of natural ecosystems require planning that addresses the complexity of social-ecological systems.